INKULKASI NILAI MULTIKULTURAL PADA SANTRI PONDOK PESANTREN AL-HASANI AL LATIFI KAUMAN BONDOWOSO - Miftahus Salam; Moh. Irmawan Jauhari (Universitas Islam Lamongan, 2021)
Inculcation is a systematic effort to inculcate value. In this case, the planting of multicultural values is targeted using the inculcation theory so that it can be seen what the actual steps of inculcation are at the Al Hasani Al Latifi Islamic Boarding School. Where the pesantren is famous for its ability to manage the diversity that exists in the pesantren and in the Kauman community of Bondowoso City. This research uses a qualitative approach and the type is a case study. The data analysis used is the theory of Miles B. Huberman with data condensation, verification, and data presentation activities. The results are, first, in stimulus values, the active role of caregivers and clerics is clear and large. Second, the values discussed have four multicultural values that are emphasized at the Al Hasani Al Latifi Islamic Boarding School. These values are tolerance, democracy, equality and justice. Third, multicultural living values at the Al Hasani Al Latifi Islamic Boarding School involve several parties such as caregivers, religious teachers, pesantren residents to the Kauman community. Caregivers with the support of the ustadz are figures who play a role in grounding the multicultural values of the santri in the pesantren. Caregivers and clerics provide habituation